Inadequate neuraxial anaesthesia in patients undergoing elective caesarean section: a systematic review. (22nd January 2022) - Patel, R.; Kua, J.; Sharawi, N.; Bauer, M.E.; Blake, L.; Moonesinghe, S. R.; Sultan, P.
Summary: Neuraxial anaesthesia is widely utilised for elective caesarean section, but the prevalence of inadequate intra‐operative anaesthesia is unclear. We aimed to determine the prevalence of inadequate neuraxial anaesthesia for elective caesarean section; prevalence of conversion from neuraxial anaesthesia to general anaesthesia following inadequate neuraxial anaesthesia; and the effect of mode of anaesthesia. We searched studies reporting inadequate neuraxial anaesthesia that used ≥ ED95 doses (effective dose in 95% of the population) of neuraxial local anaesthetic agents. Our primary outcome was the prevalence of inadequate neuraxial anaesthesia, defined as the need to convert to general anaesthesia; the need to repeat or abandon a planned primary neuraxial technique following incision; unplanned administration of intra‐operative analgesia (excluding sedatives); or unplanned epidural drug supplementation. Fifty‐four randomised controlled trials were included (3497 patients). The overall prevalence of requirement for supplemental analgesia or anaesthesia was 14.6% (95%CI 13.3–15.9%); 510 out of 3497 patients. The prevalence of general anaesthesia conversion was 2 out of 3497 patients (0.06% (95%CI 0.0–0.2%)). Spinal/combined spinal–epidural anaesthesia was associated with a lower overall prevalence of inadequate neuraxial anaesthesia than epidural anaesthesia (10.2% (95%CI 9.0–11.4%), 278 out of 2732 patients vs. 30.3% (95%CI 26.5–34.5%), 232 out of 765 patients). Further studies are needed to identify risk factors, optimise detection and management strategies and to determine long‐term effects of inadequate neuraxial anaesthesia.